El dolo: ¿fenómeno espiritual o atribución normativa? - Sánchez Málaga Carrillo, Armando (2015)
Mens Rea is a figure of Criminal Law which is very difficult to determine, especially if it is intended to appreciate the intention that a person has while commiting a crime, as well as the difference between intent and guilt is not clear in many cases.For that reason, the author of this article explains different theories that aim to determine when intent exists. Some of these theories are centered in objective factors (normative), which come from the law; and other theories are centered in internal, subjective factors (psychological). Then, the author presents the problems that affect each of the mentioned theories and explains what should be taken into account to elaborate a more efficient theory of Mens Rea.